Lung protective ventilation guided by driving pressure improves pulmonary outcomes in heart transplantation - Mei-fang Chen; Lin-feng Xie; Xin-fan Lin; Ping-ping Wu; Jia-xin Zhang; Yong Lin (Scientific Reports)
Abstract This study aimed to investigate whether driving pressure-guided ventilation can reduce postoperative pulmonary complications in patients who have undergone heart transplantation. Patients who underwent orthotopic heart transplantation were divided into two groups according to the perioperative ventilation strategy: (1) conventional lung-protective ventilation (group C) and (2) driving pressure-guided ventilation (group D). The primary outcome was the occurrence of postoperative pulmonary complications within 30 days of surgery. Univariate and multivariate logistic regression analyses were performed to evaluate the independent risk factors associated with postoperative pulmonary complications (PPCs). Compared with group C, patients in group D exhibited lower driving pressure. Oxygenation improved significantly in the early period after surgery in patients in group D. Group C exhibited a higher number of patients with postoperative pulmonary complications, especially respiratory infections and atelectasis. Patients in group D experienced a shorter duration of postoperative mechanical ventilation and a shorter stay in the intensive care unit. The conventional ventilation strategy, the high driving pressure level and the low PaO2 value at the end of the surgery were the independent risk factors for PPCs in heart transplantation. Compared with conventional lung-protective ventilation, driving pressure-guided ventilation was associated with improved pulmonary oxygenation and lower incidences of pulmonary complications among patients after heart transplantation.